Direct-write piezoelectric coating transducers in combination with discrete ceramic transducer and laser pulse excitation for ultrasonic impact damage detection on composite plates. (July 2022) - Philibert, Marilyne; Chen, Shuting; Wong, Voon-Kean; Liew, Weng Heng; Yao, Kui; Soutis, Constantinos; Gresil, Matthieu
In this work, direct-write piezoelectric transducers (DWTs) were made by spraying piezoelectric poly(vinylidene fluoride-co-trifluoroethylene) coating with comb-shaped electrodes on carbon fibre reinforced polymer (CFRP) plates for drop weight impact damage detection. Their ability and performance were investigated and compared to discrete piezoelectric lead zirconate titanate (PZT) ceramic transducers that were adhesively bonded on the same CFRP plate. Guided wave signals were acquired with different combinations of actuator-sensor involving DWT, PZT and laser ultrasonic excitation, in pitch-catch configuration. DWTs allowed consistency and simplified signal interpretation due to an effective mode selection (A0 or S0 mode) with wavelengths of 10 and 12 mm. PZTs generated stronger but much more complex signals and mode selection with a larger wavelength (20 mm). The configuration with PZT as actuator and DWT as receiver showed the highest signal amplitude changes of A0 or S0 mode, allowing efficient detection of damage introduced by a 31 J impact. Further ultrasonic B- and C-scans revealed a 27 mm long crack on the plate's backside developed in addition to internal cracks and delaminations of about 34 mm in length. For realizing contactless ultrasound excitation, a neodymium-doped yttrium aluminium garnet laser (wavelength of 1064 nm, 5.4 ns pulses) was used to replace the surface-mounted brittle PZT. The combination of the broadband laser excitation with the DWTs as sensors achieved more reliable damage detection than equivalent PZTs, attributed to DWT's effective single mode selection. In addition to reduced weight, the polymeric coated DWTs allow large area implementation (scaling up), even on curved surfaces due to their flexibility and conformability, in contrast to adhesively bonded discrete transducers.